Conceptual Framework of Healthy Divorce in Iran: A Qualitative Study - Amiri Siavashani, Samaneh; Namvar, Hooman; Ghorban Jahromi, Reza (Applied Family Therapy Journal (AFTJ), 2026)
Objective: This study aimed to develop and validate a culturally grounded, multidimensional conceptual framework of healthy divorce in Iran by identifying and prioritizing the biological, psychological, social, cultural, ethical, and spiritual factors shaping the divorce process.Methods and Materials: The study employed a qualitative, integrative design combining systematic literature review, qualitative content analysis, semi-structured interviews, and the fuzzy Delphi method. Participants included experts in family and divorce studies from psychology, social sciences, and social work, as well as married, divorcing, and divorced individuals selected through purposive sampling. Initial indicators were extracted from Persian and English literature and refined through expert consensus. Pairwise comparisons were conducted to calculate fuzzy weights for indicators within each dimension, followed by defuzzification to determine their relative importance. Thematic analysis was used to analyze interview data, and methodological triangulation ensured the credibility and rigor of findings.Findings: The results indicated that healthy divorce is a dynamic outcome of interaction among six dimensions. Psychological factors showed the strongest influence, particularly psychological problems, hardiness, irrational beliefs, and differentiation of self. In the biological dimension, chronic physical illness, addiction, and sexual dissatisfaction were most salient. Social competence, moral–behavioral violence, and communication skills emerged as key social determinants. Cultural factors were dominated by adverse life events, family interference, and value differences. Ethical factors, especially lack of commitment and infidelity, held the highest weights overall. The spiritual dimension, although not weighted due to its single-indicator structure, functioned as a regulating conceptual component in the final model.Conclusion: Healthy divorce in Iran should be understood not as the absence of conflict or a purely legal resolution, but as a multidimensional, ethically grounded, and culturally embedded process whose quality depends on the effective management of individual, relational, and contextual resources.